Coevolution of climate, demography and food systems in North and South America - Freeman, Jacob (2017)
One of the less well-understood problems in paleoscience is the role of climate as a modulator of long-term changes in human demography, and, in turn, how changes in human demography influence climate because demography also determines how individuals choose to modify ecosystems. Our workshop compared the long-term interaction between climate, human population change and the organization of social systems to understand the coevolution of Social and Ecological Systems (SES). The feedbacks between climate, ecosystems and social systems may lead to threshold changes in the organization of SES (Anderies et al. 2013). Paleoscience is critical for understanding how and when interactions between climate, ecosystems, and human systems reach threshold-state changes. Such understanding is important because contemporary SES must adapt to population growth and climate change, and insights gained from past SES may informsustainable development in the contemporary world.